The Slaughter Man - Parsons, Tony (London Arrow Books, 2015)
On New Year's Day, a wealthy family is found slaughtered inside their exclusive gated community in north London, their youngest child stolen away. The murder weapon - a gun for stunning cattle before they are butchered - leads Detective Max Wolfe to a dusty corner of Scotland Yard's Black Museum devoted to a killer who - 30 years ago - was known as the Slaughter Man. But the Slaughter Man has done his time, and is now old and dying. Can he really be back in the game?
Keywords: England--London -- Serial murder investigation -- Murder--Investigation